Epistemologi Empirisme - Fitri, Nurul Amalia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Knowledge is a fundamental aspect of human life. One branch of philosophy that discusses knowledge is epistemology. In the development of philosophy, there are various schools of thought that try to explain how knowledge is obtained, and two of the most influential are rationalism and empiricism. This study is a literature review with a qualitative descriptive approach. The main data in this study is literature data used to see the epistemology of empiricism in the philosophy of science. The data collected is coded, then reduced and finally conclusions are drawn based on qualitative analysis. The results of the study show that Epistemology is a branch of philosophy that studies knowledge, its origins, limitations, and truth. In epistemology, there are fundamental questions such as: "What do we know?", How do we know something?", and "What makes knowledge valid?" Epistemology discusses concepts such as legitimate belief, justification, and truth, as well as various theories about how to acquire knowledge. Empiricism is one school of thought in epistemology that states that knowledge comes from sensory experience or direct observation of the world. According to empiricism, all knowledge we have comes from data obtained through the senses, such as sight, hearing, or touch.